The role of MOZ/KAT6A in hematological malignancies and advances in MOZ/KAT6A inhibitors. (December 2021) - Su, Jingtian; Wang, Xuan; Bai, Yuwei; Sun, Moran; Yao, Yongfang; Duan, Yongtao
Abstract: Hematological malignancies, unlike solid tumors, are a group of malignancies caused by abnormal differentiation of hematopoietic stem cells. Monocytic leukemia zinc finger protein (MOZ), a member of the MYST (MOZ, Ybf2/Sas3, Sas2, Tip60) family, is a histone acetyltransferase. MOZ is involved in various cellular functions: generation and maintenance of hematopoietic stem cells, development of erythroid cells, B-lineage progenitors and myeloid cells, and regulation of cellular senescence. Studies have shown that MOZ is susceptible to translocation in chromosomal rearrangements to form fusion genes, leading to the fusion of MOZ with other cellular regulators to form MOZ fusion proteins. Different MOZ fusion proteins have different roles, such as in the development and progression of hematological malignancies and inhibition of cellular senescence. Thus, MOZ is an attractive target, and targeting MOZ to design small-molecule drugs can help to treat hematological malignancies. This review summarizes recent progress in biology and medicinal chemistry for the histone acetyltransferase MOZ. In the biology section, MOZ and cofactors, structures of MOZ and related HATs, MOZ and fusion proteins, and roles of MOZ in cancer are discussed. In medicinal chemistry, recent developments in MOZ inhibitors are summarized. Graphical Abstract: ga1